1998
DOI: 10.1128/aac.42.9.2417
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics of Meropenem during Continuous Venovenous Hemofiltration

Abstract: The pharmacokinetic properties of meropenem were investigated in nine critically ill patients treated by continuous venovenous hemofiltration (CVVH). All patients received one dose of 1 g of meropenem intravenously. High-flux polysulfone membranes were used as dialyzers. Meropenem levels were measured in plasma and ultrafiltrate by high-performance liquid chromatography. The total body clearance and elimination half-life were 143.7 ± 18.6 ml/min and 2.46 ± 0.41 h, respectively. The post- to prehemofiltration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 21 publications
6
37
0
Order By: Relevance
“…The dialysatebased estimates of dialysis clearance and the fraction removed for meropenem were too low in comparison with the dialysis clearance estimated from drug concentrations before and after application of the dialysis membrane. A possible explanation for this observation (already described previously) could be adsorption of meropenem by the dialysis membrane (25) or instability of meropenem in the dialysate.…”
Section: Discussionmentioning
confidence: 86%
“…The dialysatebased estimates of dialysis clearance and the fraction removed for meropenem were too low in comparison with the dialysis clearance estimated from drug concentrations before and after application of the dialysis membrane. A possible explanation for this observation (already described previously) could be adsorption of meropenem by the dialysis membrane (25) or instability of meropenem in the dialysate.…”
Section: Discussionmentioning
confidence: 86%
“…In these studies, CRRT caused more than 50% of meropenem CL total when a higher CRRT intensity was used (effluent flow rate N70 mL/min) (Bilgrami et al, 2010;Giles et al, 2000;Isla et al, 2005;Kielstein et al, 2006;Krueger et al, 1998Krueger et al, , 2003Langgartner et al, 2008;Robatel et al, 2003;Seyler et al, 2011;Tegeder et al, 1999;Thalhammer et al, 1998;Ververs et al, 2000). Substantial clearance of meropenem was also observed during PIRRT (Deshpande et al, 2010;Kielstein et al, 2006).…”
Section: Carbapenemsmentioning
confidence: 79%
“…Variations in RRT settings, such as type of filter material, blood flow rate and effluent flow rate settings can result in changes to antibiotic pharmacokinetics, (Choi et al, 2004;Lam et al, 2010;Tegeder et al, 1999;Thalhammer et al, 1998). In general, when higher RRT intensities are used (i.e.…”
Section: Renal Replacement Therapy In Icumentioning
confidence: 96%
“…Studies of patients on CRRT receiving MEM have proposed doses ranging from 500 mg every 12 hours [42,43] to 1 g every 12 hours [20,44]. In nine septic patients, the V d was 29.5 ± 2.7 l ( V d = 39.7 l (14.8 to 184.7 l) in the present study), the AUC was 118.0 ± 15.8 mg/hour/l, the total CL was 143.7 ± 18.6 ml/minute (total CL = 88.7 ml/minute (43.2 to 205.7 ml/minute) in the present study) and the t 1/2 was 2.33 ± 0.38 hours [42]. On the basis of a literature review, Trotman and colleagues suggested doses of 1 g every 12 hours for CVVH or CVVHDF [16].…”
Section: Discussionmentioning
confidence: 99%